2015
DOI: 10.1055/s-0034-1392418
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of post-ERCP pancreatitis in patients with suspected sphincter of Oddi dysfunction undergoing biliary or dual sphincterotomy: results from the EPISOD prospective multicenter randomized sham-controlled study

Abstract: The performance of biliary or dual sphincterotomy does not increase the risk of PEP in patients suspected of SOD. However, the high rate of PEP in patients with suspected SOD, despite pancreatic stenting in expert centers, is confirmed in this prospective study. The combined effect of duration of ERCP and sedation type on the development of PEP should be further explored.Clinicaltrials.gov registration: NCT00688662.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 12 publications
(16 reference statements)
1
19
1
2
Order By: Relevance
“…Pancreatic stent placement was reported to be effective in the reduction of PEP in SOD . In contrast to these reports, there are some reports that pancreatic stenting cannot reduce the incidence of PEP . The present study showed that pancreatic stent placement was a risk factor for PEP in univariate analysis.…”
Section: Discussioncontrasting
confidence: 72%
See 2 more Smart Citations
“…Pancreatic stent placement was reported to be effective in the reduction of PEP in SOD . In contrast to these reports, there are some reports that pancreatic stenting cannot reduce the incidence of PEP . The present study showed that pancreatic stent placement was a risk factor for PEP in univariate analysis.…”
Section: Discussioncontrasting
confidence: 72%
“…Pancreatic stenting is considered effective for prevention of PEP in SOD patients . However, in the EPISOD trial, pancreatic stenting could not sufficiently prevent PEP in suspected SOD type 3 patients . Is pancreatic stenting effective for the prevention of PEP in Japanese patients with many of type 1 and type 2 SOD cases?…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There were no significant differences noted in migration rates between the participating centers, suggesting this was not related to differences in technique or follow‐up protocols. The overall migration rate is lower than observed at comparable times in similar studies; for example, in the EPISOD trial, the retained stent rate was 10% after a median of 24 days . Reasons for the observed migration rate remain unexplained.…”
Section: Discussionmentioning
confidence: 60%
“…It should be emphasized that assessment of PPS migration was not prescribed per protocol in the immediate post‐PPS placement days; hence, observation of PPS migration was based on a wide range of assessment time points per local practice of patient follow up. Interestingly, other studies reported superiority of shorter 3‐cm 5‐Fr pancreatic stents compared to longer 5‐cm 5‐Fr stents in preventing PEP, yet the opposite conclusion was reached when comparing >3 cm 4‐Fr pigtail stents to <3 cm 4‐Fr straight stents . Clearly, the recommended prophylactic PPS length needs to be further defined.…”
Section: Discussionmentioning
confidence: 99%